HOLISTIC PERFORMANCE MEASUREMENT TO ACHIEVE SUSTAINABLE COMPETITIVE ADVANTAGE - Keni Keni (Jurnal Manajemen., 2013)
In the past, companies used balanced scorecard to measure its performance. Now, balanced scorecard as a performance measurement tool is no longer sufficient because business has been affected by changes to the natural environment and developing social expectations. In order to achieve sustainable competitive advantage, companies are beginning to address the risks and opportunities associated with these changes in their longer-term business planning. To turn risks into opportunities, companies have increasingly integrated environmental considerations and corporate social responsibility into mainstream business management and measurement processes.